2022
DOI: 10.1002/sres.2831
|View full text |Cite
|
Sign up to set email alerts
|

A systems view of responding to the COVID‐19 pandemic: A causal loop model for Taiwan's approach

Abstract: Since the worldwide outbreak of the COVID-19 pandemic in December 2019, Taiwan has successfully stopped the spread of COVID-19. The policies and works of the epidemic control are a complex and dynamic process. This study applied the methodology of system dynamics to explore the structure of the COVID-19 epidemic control system in Taiwan and analysed its system behaviours. The results show that the system is composed of key subsystems, such as national health insurance and quarantine, combined with government p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Moreover, 38.4% and 25.6% of the HCWs obtained IES-R scores of ≥24 and ≥33, respectively. The risks of traumatic stress and PTSD in the HCWs do not differ considerably from those observed in other countries, although the peak of the pandemic occurred one year later [5,11,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. This indicates that although HCWs in Taiwan had an extra year to prepare for the pandemic, when the pandemic became severe, the increase in the number of patients increased their care responsibilities, resulting in greater stress on the HCWs and negatively affecting their mental health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, 38.4% and 25.6% of the HCWs obtained IES-R scores of ≥24 and ≥33, respectively. The risks of traumatic stress and PTSD in the HCWs do not differ considerably from those observed in other countries, although the peak of the pandemic occurred one year later [5,11,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. This indicates that although HCWs in Taiwan had an extra year to prepare for the pandemic, when the pandemic became severe, the increase in the number of patients increased their care responsibilities, resulting in greater stress on the HCWs and negatively affecting their mental health.…”
Section: Discussionmentioning
confidence: 99%
“…The pandemic situation subsided within two months, with the number of new infections dropping to between 10 and 20 per day. On 27 July 2021, because of the gradual easing of the pandemic, the pandemic alert was lowered to Level 2 [5,6]. From May to July 2021-the period of the first wave pandemic's peak-14,574 new cases and 829 deaths occurred in Taiwan [3].…”
Section: Introductionmentioning
confidence: 99%
“…The proposed model focused on reducing contacts during the epidemic, and the case study examined the three cities of Tokyo, Osaka, and Hokkaido. Lee et al used a system dynamics model to examine the control system of COVID-19 in Taiwan and studied its system behaviors [ 47 ]. They concluded that six critical loops created the epidemic control system in Taiwan.…”
Section: Literature Reviewmentioning
confidence: 99%